Ten years of institutional consolidation of AMEXCID and the link with other actors - Pérez-Pineda, Jorge A.; Vargas, Elizabeth; Urbano Reyes, Javier (Revista Española de Desarrollo y Cooperación, 2021)
Under the ten years framework from the approval of the law of international development cooperation in Mexico, the creation of its Agency (AMEXCID), and pillars of the Mexican system of cooperation, it is addressed the experience of the agency with three key actors for an effective cooperation, Academy, private sector and migrants. The paper recognizes the relevance of the multiactor partnerships and dialogue.